Makna Ragam Hias Topeng Kayu Labuapi Lombok dan Implementasinya Pada Modul Materi Pembelajaran Seni Budaya SMP - Tesa Yustika; Pyo Apriliana Munawarah; Mi’Rajus Subyan Rahmat (Journal of Mandalika Literature, 2025)
This study aims to: (1) Examine the meaning of decorative motifs on Labuapi wooden masks from West Lombok. (2) Develop a learning module on the decorative motifs of Labuapi wooden masks for cultural arts students at MTs Negeri 1 Mataram. (3) Assess the feasibility of using the learning module on the decorative motifs of Labuapi wooden masks for students at MTs Negeri 1 Mataram. (4) Evaluate the effectiveness of the learning module on the decorative motifs of Labuapi wooden masks for students at MTs Negeri 1 Mataram.This research employs two methods: qualitative and R&D (Research and Development). The qualitative method aims to examine the meaning of the decorative motifs on Labuapi wooden masks, while the R&D method focuses on developing an educational product and testing its feasibility and effectiveness for teaching the decorative motifs of Labuapi wooden masks.The research findings are as follows: (1) Overall, the meaning of the decorative motifs on Labuapi wooden masks is derived from the daily life and customs of the Labuapi community in West Lombok. (2) The development of the learning module on the decorative motifs of Labuapi wooden masks follows the Borg and Gall model, which includes needs analysis, planning, initial product format development, initial field testing, main product revisions, operational field testing, operational product revisions, and final product testing. (3) The feasibility of the Labuapi wooden mask learning module, as evaluated by subject matter experts, scored a percentage of 93.90%, media experts 93.75%, teachers 98.08%, and students 89.24%. Therefore, the developed module is deemed suitable for use in cultural arts education. (4) Based on the analysis of pre- and post-test results on knowledge and skills, there is a significant difference before and after using the learning module on the decorative motifs of Labuapi wooden masks, demonstrating its effectiveness